2021
DOI: 10.5114/wiitm.2021.103303
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography-guided core needle biopsy for lung nodules: low-dose versus standard-dose protocols.

Abstract: Introduction: Computed tomography (CT)-guided core needle biopsy (CNB) is an essential step in the management of lung nodules (LNs). Low-dose CT (LDCT)-guided CNB has been used to decrease the radiation exposure. Aim: To evaluate the technical success, safety, diagnostic capacity, and radiation exposure to patients between LDCT-guided and standard-dose CT (SDCT)-guided CNB for LNs. Methods: This is a retrospective, single-centre study. Patients who underwent LDCT-guided or SDCT-guided CNB for LNs from January … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 17 publications
4
17
0
Order By: Relevance
“…We found that the diagnostic yield of CT-guided CNB was not reduced by the low-dose CT. Furthermore, the diagnostic yield rates in both groups (68% and 65%) were similar to past investigations regarding CTguided CNB for LNs [9,17]. Similarly, Shpilberg et al [16] additionally revealed that low-dose CT did not reduce diagnostic yield for spine biopsies (low-dose group: 69%; standard-dose: 60%, P = 0.60).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…We found that the diagnostic yield of CT-guided CNB was not reduced by the low-dose CT. Furthermore, the diagnostic yield rates in both groups (68% and 65%) were similar to past investigations regarding CTguided CNB for LNs [9,17]. Similarly, Shpilberg et al [16] additionally revealed that low-dose CT did not reduce diagnostic yield for spine biopsies (low-dose group: 69%; standard-dose: 60%, P = 0.60).…”
Section: Discussionsupporting
confidence: 85%
“…Resection could make the nal diagnoses for both malignant and benign LNs. CNB-based malignancy and speci c benignity could be accepted as the nal diagnosis [8][9][10][11][12][13]. CNB-based suspected malignancy and non-speci c benignity could not be accepted as the nal diagnoses, if they were not con rmed by resection, the CT medical observation would be useful for attaining a nalized diagnostic outcome.…”
Section: De Nitions and Diagnosesmentioning
confidence: 99%
See 2 more Smart Citations
“…Sensitivity values were impacted by the reference standard used in included studies (P = 0.02), with higher sensitivity values being reported when the references standard included surgery and biopsy samples. While benign are SPNs are generally confirmed via surgical resection, malignancy SPNs can be confirmed via both surgery and biopsy [ 34 ]. When researchers only focused on surgically-confirmed SPNs in their studies, this markedly reduced the malignant SPN sample size, thereby constraining the sensitivity of the resultant models.…”
Section: Discussionmentioning
confidence: 99%